2015
DOI: 10.1111/jopr.12414
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of TMD in Polish Young Adults

Abstract: Muscle disorders were most frequently diagnosed in the group of Polish young adults, and the prevalence of the disease did not differ across similar groups of young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 20 publications
4
45
0
2
Order By: Relevance
“…However, the prevalence of TMDs in students reported from different countries varies substantially. According to previous studies reported in European countries, the detection rates of TMDs were 26.5% in Poland (Loster et al, ) and 22.58% in Italy (Tecco et al, ), which is slightly less than the rate observed in China. In contrast, we observed higher prevalence rates in Middle Eastern and South American countries, including 34.9% in Brazil, 34.7% in Iran, and 46.8% in Riyadh (Bertoli et al, ; Ebrahimi, Dashti, Mehrabkhani, Arghavani, & Daneshvar‐Mozafari, ; Habib et al, ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the prevalence of TMDs in students reported from different countries varies substantially. According to previous studies reported in European countries, the detection rates of TMDs were 26.5% in Poland (Loster et al, ) and 22.58% in Italy (Tecco et al, ), which is slightly less than the rate observed in China. In contrast, we observed higher prevalence rates in Middle Eastern and South American countries, including 34.9% in Brazil, 34.7% in Iran, and 46.8% in Riyadh (Bertoli et al, ; Ebrahimi, Dashti, Mehrabkhani, Arghavani, & Daneshvar‐Mozafari, ; Habib et al, ).…”
Section: Discussionmentioning
confidence: 74%
“…The prevalence of TMDs reported in different countries varies substantially, with reported prevalence rates of 26.5% in Poland (Loster, Osiewicz, Groch, Ryniewicz, & Wieczorek, ) and 13.0% in Germany (Wu & Hirsch, ). However, few studies have reported the prevalence of TMDs in China prior to 1979.…”
Section: Introductionmentioning
confidence: 99%
“…N N403 589138. 12 All images were obtained with the same ProMax ® scanner (Planmeca, Helsinki, Finland 2005), by the same radiology technician, using the same radiation parameters in current (14.0 mA) and voltage (70 kV). 7 A stomatognathic system examination was performed in all project participants by one calibrated examiner in accordance with the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD).…”
Section: Methodsmentioning
confidence: 99%
“…Data regarding the maximum range of the mandible opening (pain-free opening), midline coincidence between upper and lower incisors in a centric occlusion position, range of vertical incisal distance, and curve of movement path were obtained from the RDC/ TMD Axis I Clinical Examination Form after clinical examination was done by a single calibrated specialist in prosthodontics (MG). 12 The study inclusion criteria included the following: no symptoms of temporomandibular disorders according to RDC/TMD, no midline deviation, and a straight line of the mandibular opening.…”
Section: Methodsmentioning
confidence: 99%
“…These volunteers were free of the signs and symptoms of temporomandibular disorders, as determined by the Polish version of the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) questionnaire; they also possessed intact dentition. 16,17 All the participants expressed their unforced consent to participate in the study and signed the appropriate statement. The examination was performed in accordance with the Declaration of Helsinki and Good Clinical Practice (GCP).…”
Section: Methodsmentioning
confidence: 99%